Implantación de un sistema de contabilidad y aplicación de indicadores financieros en el centro de copiado J & J de la ciudad de Loja, periodo noviembre - diciembre del 2015 - Arias Torres, Karina Cecibel (2017)
The development of the present thesis was carried out with the main purpose of fulfilling one of the requirements established in the Regulation of Academic Regime of the National University of Loja; as well as establishing the accounting system in the J & J Copying Center; so that the current economic-financial condition can be known in a real and timely manner. This is also providing the owner with an effective and efficient control tool in dayto- day operations; also achieving maximum use of the resources available in each of the business areas. To comply with the objectives proposed in the thesis project; it began with the fulfillment of the organization of the source documents, in order to establish the Plan and Manual of accounts, according to the current accounting regulations for this type of business, so that each of the accounting accounts that were used was codified and detailed. in the development of the accounting process. Within the accounting process after the organization of the documents, we proceeded with the detail of the Initial Inventory, with this information the values were grouped and the Initial Situation Statement was executed; thus developing the Memorandum of Operations that served as the basis for journaling in the Daily Book in a chronological manner, Major Books, Checking Balance, until the presentation of the Financial Statements; applying the liquidity, efficiency and indebtedness indicators. Once the present research work was completed, the conclusions and recommendations were developed; where all the relevant operations of the implementation of the accounting system are summarized in order to improve and achieve a positioning in the business market, using the available resources effectively and efficiently.